The protection of family unity in contexts of migration crisis: a tale of two cases - La Spina, Encarnación (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2017)
In the current context of migration crisis, the main challenge facing European states is the coherent implementation of immigration and asylum system according to the international standards of human rights. This paper proposes a retrospective on the dissimilar protection of the right to family unity in cases of migrant workers and asylum seekers that require special attention, due to the reasons that forced them to runaway to their country and avoid them to manage their family life. Thus, reviewing two recent cases it is proposed to assess the scope of the limits established by family unit right against the limitations imposed ex lege by the immigration and asylum rules in Spain.doi: https://doi.org/10.20318/universitas.2017.3561
Keywords: asylum; immigration; Human Rights; family unit; Spain; European Union